Time-Restricted Feeding in Mice Prevents the Disruption of the Peripheral Circadian Clocks and Its Metabolic Impact during Chronic Jetlag - Louis Desmet (MDPI AG, 2021)
We used time-restricted feeding (TRF) to investigate whether microbial metabolites and the hunger hormone ghrelin can become the dominant entraining factor during chronic jetlag to prevent disruption of the master and peripheral clocks, in order to promote health. Therefore, hypothalamic clock gene and Agrp/Npy mRNA expression were measured in mice that were either chronically jetlagged and fed ad libitum, jetlagged and fed a TRF diet, or not jetlagged and fed a TRF diet. Fecal short-chain fatty acid (SCFA) concentrations, plasma ghrelin and corticosterone levels, and colonic clock gene mRNA expression were measured. Preventing the disruption of the food intake pattern during chronic jetlag using TRF restored the rhythmicity in hypothalamic clock gene mRNA expression of Reverbα but not of Arntl. TRF countered the changes in plasma ghrelin levels and in hypothalamic Npy mRNA expression induced by chronic jetlag, thereby reestablishing the food intake pattern. Increase in body mass induced by chronic jetlag was prevented. Alterations in diurnal fluctuations in fecal SCFAs during chronic jetlag were prevented thereby re-entraining the rhythmic expression of peripheral clock genes. In conclusion, TRF during chronodisruption re-entrains the rhythms in clock gene expression and signals from the gut that regulate food intake to normalize body homeostasis.